The teory of Scientific Research on Innovation in the Tourism Industry - Tukibayeva К.Б.; Zhanseitova Г.С.; Bakirbekova А.М. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2023)
The strengthening of economic growth and the desire to increase competitive advantages in the conditions of the tourist market contributes to the improvement of innovation using a system of innovations based on science and practice. Therefore, Kazakhstan needs to study the innovative progress and implement its results to enter the number of competitive countries in the world and to develop the tourism industry in a new dynamic. In the article author analyzed and consistently systematized the research of innovations and innovative activity in the sphere of tourism, the works of scientists who formed the conceptual basis of innovations in tourism, their scientific achievements, directions and results of research. In addition, the scientific article is devoted to the classification features of innovation in tourism, economic, financial, scientific and technical resource, social, environmental efficiency of innovation. The author carefully studied the theoretical aspects of innovation in tourism, revealed the relevance of this topic.